Online Practices of the Economic Behavior of Russian Women during Maternity Leave] - Anastasia Shvetsova; Irina Sorokina; Алена Obolenskaya; Marina Krivoshchekova (Journal of Economic Sociology, 2022)
The article analyzes the increasing importance of visual media content in the daily life of Russian women with children under the age of 3 and suggests methods for studying visual social networks, both graphic and intertextual content. Based on the theory of social construction of gender, the authors introduce the concept of “non-maternal practices of young mothers”, defining it as a set of actions performed by women during maternity leave and aimed at meeting their social, economic, psychological needs that arise from the disappearance of the usual rhythm of life. A significant part of these practices is implemented in the online space, which makes it possible to resolve the problem of their social isolation during this period. We analyzed 720 social media accounts to understand what the thematic field of the modern mother community is and what types of economic activity are implemented in it. The results of the study represent a classification of online practices of young mothers implemented in social networks and aimed at obtaining an economic effect. The classification is based on the principle of dominant agency: real or virtual. A feature of the first group is the choice of practices aimed at creating a product or providing services in direct interaction with the consumer (food production, clothing manufacturing, hairdressing and cosmetology services, education, and creative crafts), and the social network acts aimed at promoting a product or service. The second group focuses on the direct use of the digital environment as an economic resource (blogging, online consultations, network marketing). Most practices spring from women’s desire for communication, self-realization, and earnings, which is understandable in terms of gender analysis and economic realities. However, some actions may have problematic sociocultural consequences. The riskiness of the digital environment is associated with psychological consequences, including the formation of Internet addiction, as well as negative economic effects (the vulnerability of young mothers to Internet fraud, the discrepancy between time and labor costs, and the profit received). The main conclusion of the article is that the study of women’s online economic practices during maternity leave with a focus on non-maternity practices is a promising and strategically important area of research in the landscape of modern motherhood.